Root canal morphologies of mandibular premolars in Southeast Anatolian population: Evaluation of CBCT - Yüzer Güney Mustafa; Sadullah Kaya (Balkan Stomatological Society, 2022)
Background/Aim: This study aimed to evaluate the root canal morphology of mandibular first and second premolars with the aid of cone-beam computed tomography (CBCT) in the Southeast Anatolian population. Material and Methods: The study examined a total of 1258 mandibular first and second premolars using cone-beam computed tomography images of 370 randomly selected patients who applied to the Department of OralDental and Maxillofacial Radiology of Faculty of Dentistry, Dicle University due to various indications. The total number of roots and root canals, canal symmetry and correlations between the right and left side of the mandible, and the prevalence in men and women were recorded. Data was analzyed using the Chi-Square and Fisher's Exact tests. Canal configurations were evaluated based on the Vertucci classification. Results: The evaluation of CT images of a total of 370 individuals showed that 88.89% of the first premolars and 98.45% of the second premolars were symmetrical. The canal anatomy of the first premolars suggested that 85.98% of the premolars were of Type I, 12.02% were of Type V, and 2% were of Type III based on the Vertucci classification. On the other hand, the canal anatomy of the second premolars revealed that 98.83% were of Type I, 0.67% were of Type V, and 0.5% were of Type III. Conclusions: The prevalent morphology of the multiple canals was Type V, except for the Vertucci classification Type I in the mandibular first premolars. Limited number of canal variations were observed in the mandibular second premolars.